Pengembangan Media Big Book Untuk Meningkatkan Kemampuan Membaca Siswa Kelas Awal MINU Ngingas Waru Sidoarjo - Solchan Ghazali; M. Amin; Wulan Suci Nur Rahmawati; Grisa Anecy (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
The purpose of this study was to develop big book media to improve the reading skills of early grade students at Madrasah Ibtidaiyah Nahdlatul Ulama (MINU) Ngingas Waru Sidoarjo. The research method used is development research developed by Borg and Gall. There are four stages of development carried out in this study, namely: initial data collection, planning, development, and validation and testing. The results showed that the students' reading skills were very good. In the initial data of 39% reading skills and when intervened using big book media in the third trial stage, data obtained 85 percent of the average reading skills of students. So it can be concluded that the effectiveness of using big books is very good with a 46 percent increase in the level of reading skills of early grade students who have reading difficulties.